Appraisal of the health of new Entrants Into the workplace – the APPRENTICE study. (19th October 2011) - Lam, Kin Bong Hubert; Henderson, John; Lewis, Glyn; Cullinan, Paul; Semple, Sean; Gregg, Paul; Ayres, Jon
Abstract : Objectives: Effects of work on health are well-documented but little is known about those entering the workplace for the first time (when lack of experience is important). We propose an observational study aiming to investigate the pre-employment self-selection of jobs, the lead time for the onset of illnesses, and the immediate effect of work on health (and vice versa) among young people entering the workforce for the first time. Methods: The study will be based on the Avon Longitudinal Study of Parents and Children (ALSPAC), which consists of 7000 children who have been followed-up from their birth in 1991/92, with detailed assessment on their health and other information over time. About 2000 of the participants are estimated to have started work or are seeking employment. Questionnaires are used to collect details about their job and health status at age 16 and 18 years. Results: We have received Year 16 questionnaire from the participants and are currently cleaning the dataset. Development of the Year 18 questionnaire is underway. Conclusions: Information obtained will help identify the health and safety as well as psycho-socio-cultural related considerations made by young people when choosing an occupation. We will assess the impact of work on the health of young people. The data will also allow the discovery of patterns of specific work-illness pairings, and thus would assist prevention of occupational conditions in such settings.